(untitled) (International Journal of Communication Systems and Network Technologies, 2023)
In multi rate ad hoc networks the hidden terminal problem is unique and there is a limited understanding of its effect on network performance. In this paper we studied the effects of hidden terminals in multi rate mobile ad hoc networks environments. In IEEE 802.11 base WLANs only the nodes which are within the transmission range of receiver can become the hidden nodes, where as the nodes falling within interference range of the receiver are not the part of WLAN. IEEE 802.11 standard strongly addresses the issues of those hidden nodes which are within the transmission range. In this paper we have shown that in multi rate ad hoc networks the nodes falling within the interference range can also act as hidden terminals. These hidden terminals can have detrimental effect on the performance of the multi rate ad hoc networks that can not be solved by conventional RTS/CTS mechanism of IEEE 802.11. In the present study a mechanism has been proposed by adjusting the required transmit power and maintaining receiver side Signal to Interference and Noise Ratio (SINR) above threshold value to nullify the presence of such hidden terminal. The results indicate an improved performance of multi rate ad hoc networks by employing such mechanisms.